A Study on Peer Response In A Writing Class in English Department of Muhammadiyah University of Surakarta in 2013/2014 Academic Year - Nuriyanti, Nurul (JoLLIET, 2015)
The research paper aims at finding out and describing peer response including 1) studentsâ response to their friendâs work, 2) studentsâ response to the correction, and 3) studentsâ perception about the benefits of peer response in writing class in English Department of Muhammadiyah University of Surakarta. The type of this research is case study. The subjects of this research are ten students of a writing class as the sample for the research. The methods of collecting data are observation, interview and documentation. The result of this research shows that ten students in writing subject use almost all the peer response proposed by Nelsom and Murphy. However their responses are different. The researcher finds the studentsâ responses to their friends can be classified into four categories. They are unnecessary correction (4%), accurate correction (46%), inaccurate correction (19%), and disregard(31%) from 48 data. The researcher divided two categories in studentsâ response to the correction. They are students revising the sentences and students disrgarding the correction. The last finding, the researcher finds 60% perceive of the students that peer response gives benefits; it can make their better writing. Therefore, peer response can be use as one strategy of teaching writing as proposed by Nelsom and Murphy.